Maritime communities in early medieval Wales c. AD 600-1100 - Wallbank, Beatrice (2021)
Early medieval Wales has received little attention in previous maritime studies of the Irish Sea. Those that do touch on maritime aspects of this era tend to focus on the maritime movement of goods and individuals rather than the communities who made such movement possible. This study takes such maritime communities (c.AD 600-1100) as its focus, exploring evidence for their locations, activities, cultures, status, folklore and belief systems, with a particular focus on the west coasts of Wales. The study is influenced by the interdisciplinary methods of Christer Westerdahl in exploring evidence for maritime communities and their maritime cultural landscapes. An interdisciplinary approach, including archaeological and documentary sources and literature, is particularly important in early medieval Wales where there is a lack of more obvious maritime archaeology such as boats or man-made harbour structures. The findings are then placed within their wider Irish Sea context with particular focus on the east coast of Ireland, the north coast of Cornwall and Mann. Key findings from the Welsh study areas include the significant number of early medieval burial sites overlooking or close to potential landing places, and the evidence for maritime movement of relatively low-status goods and raw materials.